Response of stream ecosystem function and structure to sediment metal: Context-dependency and variation among endpoints - David M. Costello; G. Allen Burton (Elementa: Science of the Anthropocene, 2014)
Abstract Physicochemical and ecological attributes of ecosystems (i.e., environmental context) can modify the exposure and effects of metals, which presents a challenge for ecosystem management. Furthermore, the functional and structural attributes of an ecosystem may not respond equally to metals or be uniformly responsive to environmental context. We explored how physicochemical and ecological context modified sediment metal dose-response for a suite of functional and structural measures. Two sediments with high (HB) and low (LB) acid volatile sulfide and organic carbon content (i.e., physicochemical context) were amended with copper and nickel to establish a gradient of treatments from non-toxic to potentially toxic. Sediments were deployed in each of two streams (i.e., ecological context), incubated for four weeks, and measured for sediment microbe, biofilm, and macroinvertebrate dose-response to metal. The dose-response of microbial function was affected by physicochemical context, with cotton decomposition negatively related to sediment metal only on LB sediments. The abundance of invertebrates from the orders Ephemeroptera, Plecoptera, and Trichoptera (EPT) responded negatively to sediment metal only on LB sediments; however, this dose-response was only observed in one stream, likely because of greater abundance of sensitive EPT taxa (i.e., Baetidae and Ephemerellidae). Biofilm structure was negatively affected by sediment metal in only one stream and there was no difference in dose-response between the two sediment types. Biofilm function was affected by sediment type and stream; production of biofilms exposed to HB sediment was negatively related to sediment metal in only one stream. In all, the majority of our endpoints exhibited responses that were modified by environmental context; however, each component of the ecosystem exhibited unique context dependency. For management of sediment metals, an understanding of context dependency is useful for informed decision-making, but the application of simple contextual filters are unlikely to protect all elements of an ecosystem.